Science learning management based on information technology in the context of school curriculum implementation - Mariana, Rice; Nur Sasongko, Rambat; Connie (Indonesian Journal of Educational Development (IJED), 2025)
This study aims to describe the management of science learning based on information technology at State Junior High School 1 Bengkulu Selatan. The research employed a qualitative descriptive method with purposive selection of subjects, including science teachers, the principal, the vice principals for curriculum and facilities, and students. Research data were obtained through interviews, observations, and documentation, then analysed through data reduction, presentation, verification, and conclusion drawing. The urgency of this study lies in the demand for adaptive learning management in the digital era. At the same time, many schools still face infrastructure limitations, low digital literacy, and inadequate human resources. The subjects were chosen purposively because of their direct involvement in the planning and implementation of science learning, ensuring diverse perspectives and comprehensive findings. The results showed that the management of science learning based on information technology at State Junior High School 1 Bengkulu Selatan has been applied gradually in line with curriculum demands. The school demonstrated a commitment to integrating technology into planning, implementation, and evaluation, although several challenges remain, particularly related to facilities, teacher competencies, and policy support. Various strategies and collaborations have been pursued to create a more inclusive and contextually relevant learning ecosystem. This study recommends further research to develop sustainable and scalable models of technology-based learning management and to evaluate the effectiveness of digital infrastructure policies at the junior high school level.